ISLAMIC DIGITAL FINANCE, RENEWABLE ENERGY POLICY, AND RED OCEAN STRATEGY IN SUPPORTING INDONESIA'S ECONOMIC GROWTH - Muhammad Solihin Sahal (Nurul Jadid University, 2026)
This article examines the synergy between Islamic digital finance, renewable energy policy, and Red Ocean strategy as an integrated model supporting Indonesia's inclusive and sustainable economic growth. Using a systematic literature review (SLR) design reinforced by an illustrative case study, this research constructs a four-layer Synergistic Causality Chain (SCC) model: (1) Islamic contracts (akad) as profit-sharing-based financing sources, (2) renewable energy as a transformer of production cost structures, (3) Red Ocean strategy as a converter of cost advantages into market positions, and (4) economic growth as the output of their synergy. The Wajo Silk Weaving Cooperative case illustrates that IDR 2.5 billion musyarakah financing allocated to a 50 kWp solar installation resulted in an 84% reduction in electricity costs, 38% production increase, and 80.4% revenue growth within 18 months. Findings show the three variables are asymmetrically complementary and directionally dependent. This article contributes to literature by integrating three domains Islamic finance, energy economics, and competitive strategy previously studied in isolation